Composite material and preparation method thereof, light-emitting device and display device
By connecting the ligands with a ring-like conjugated structure on inorganic particles, the problem of harsh conditions and easy oxidation of heavy metal-free quantum dot light emitting devices is solved, and the effect of improving luminescence efficiency and service life is achieved.
Patent Information
- Application Number
- CN202311153545.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-07
AI Technical Summary
The synthesis conditions of existing heavy metal-free quantum dot luminescent devices are harsh, difficult to operate, poor synthesis repeatability, and easy to be oxidized, affecting the luminescence efficiency and service life.
A composite material is used, which includes inorganic particles and ligands attached to inorganic particles. The ligand has a cyclic conjugated structure and functional groups, which can achieve coordination connection with inorganic particles, reduce the oxidation risk of the material and improve luminescence efficiency.
By modifying inorganic particles with ligands with a ring-like conjugated structure, the luminescence efficiency and service life of the light emitting device are improved, the risk of oxidation is reduced, and the stability of the material is enhanced.
Smart Images

Figure CN119584837A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of display technology, and in particular to a composite material, a method for preparing the composite material, a light-emitting device including the composite material, and a display device including the light-emitting device. Background Art
[0002] Currently, the widely used light-emitting devices are organic light-emitting diodes (OLEDs) and quantum dot light-emitting diodes (QLEDs). QLEDs have the advantages of saturated color and adjustable wavelength of emitted light, and high quantum yields of photoluminescence and electroluminescence. In recent years, they have become a strong competitor to OLEDs. The QLED device structure generally includes an anode, a hole functional layer, a light-emitting layer, an electron functional layer, and a cathode. Under the action of the electric field, the holes generated by the anode of the light-emitting diode and the electrons generated by the cathode move and are injected into the hole functional layer and the electron functional layer respectively, and finally migrate to the light-emitting layer. When the two meet in the light-emitting layer, energy excitons are generated, thereby exciting the light-emitting molecules to finally produce visible light.
[0003] At present, quantum dots containing heavy metals such as cadmium, lead, and mercury have good performance as light-emitting layer materials, but heavy metals can damage the environment and impair the function of human organs, so heavy metal-free quantum dots have always been the focus of research. At present, heavy metal-free quantum dots mainly include binary ZnS, ZnSe, and ZnTe systems of the II-VI group, ternary ZnSSe and ZnSeTe mixed systems, and InP systems of the III-V group. However, the synthesis conditions of the above-mentioned heavy metal-free quantum dots are harsh, and dangerous highly active organic metal compounds need to be used. The operation is difficult and the synthesis repeatability is poor. In addition, the quantum dots of the above-mentioned system are easily oxidized, and the storage environment requirements are high, which is not conducive to mass production. After the quantum dots are oxidized, the luminous efficiency of the light-emitting device decreases and the service life is shortened.
[0004] Therefore, the luminous efficiency of the light-emitting device needs to be further improved. Summary of the invention
[0005] In view of this, the present application provides a composite material, aiming to improve the luminous efficiency of existing light-emitting devices.
[0006] The embodiment of the present application is implemented as follows: a composite material includes inorganic particles and ligands connected to the inorganic particles, wherein the ligand has a structural formula as shown in formula (I):
[0007]
[0008] Wherein, Ar includes substituted or unsubstituted C10-C24 fused ring aromatic groups, substituted or unsubstituted C5-C24 fused ring heteroaromatic groups; the heteroatoms in the fused ring heteroaromatic groups include one or more of oxygen atoms, nitrogen atoms or sulfur atoms; the substituted substituents are selected from one or more of C1-C10 alkyl groups, C1-C10 alkenyl groups, C1-C10 alkynyl groups, C1-C10 alkoxy groups, halogen atoms, D, -CN, -NO2;
[0009] X is selected from one or more of an amino group, a carboxyl group, a thiol group or a phosphate group.
[0010] Optionally, in some embodiments of the present application, the fused ring aromatic group is composed of a cyclic group, and the cyclic group includes a benzene ring, One or more of; and / or
[0011] The aromatic ring in the fused-ring heteroaryl group includes one or more of a benzene ring, a furan ring, a pyran ring, a thiophene ring, a pyridine ring, and a pyrrole ring; and / or
[0012] X is selected from one of an amino group, a carboxyl group, a thiol group or a phosphate group; and / or
[0013] The substituted substituent is selected from one or more of C1-C6 alkyl, C1-C6 alkenyl, C1-C6 alkynyl, C1-C6 alkoxy, halogen atom, D, -CN, -NO2.
[0014] Optionally, in some embodiments of the present application, Ar has one of the following structural formulas:
[0015]
[0016] Optionally, in some embodiments of the present application, the ligand has one of the following structural formulas:
[0017]
[0018] Optionally, in some embodiments of the present application, in the composite material, the mass ratio of the inorganic particles to the ligand is (5-15):1; and / or
[0019] The average particle size of the inorganic particles is 3nm to 20nm; and / or
[0020] The material of the inorganic particles includes quantum dot luminescent materials, and the quantum dot luminescent materials include one or more of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials. The material of the single structure quantum dots, the core material of the core-shell structure quantum dots and the shell material of the core-shell structure quantum dots are independently selected from one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds. The II-VI group compounds include one or more of ZnO, ZnS, ZnSe, ZnTe, ZnSeS, ZnSeTe and ZnSTe. The IV-VI group compounds include one or more of SnS, SnSe, SnTe, SnSeS, SnSeTe and SnSTe. The III-V group compounds include GaN, GaP, GaAs, GaSb, AlP, AlAs, AlSb, InN, InP, InAs, InSb , GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound includes one or more of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material includes a doped or undoped inorganic perovskite semiconductor or an organic-inorganic hybrid perovskite semiconductor, the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ions, M is a divalent metal cation, including Sn 2+ , Cu 2+ 、Ni 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMY3, wherein B is an organic amine cation, including CH3(CH2) n-2 NH3 +or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation, including Sn 2+ , Cu 2+ 、Ni 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, Y is a halogen anion, including Cl - Br - ,I - One or more of .
[0021] Optionally, in some embodiments of the present application, in the composite material, the mass ratio of the inorganic particles to the ligand is (8-9):1; and / or
[0022] The average particle size of the inorganic particles is 8nm to 15nm.
[0023] Accordingly, an embodiment of the present application further provides a method for preparing a composite material, comprising:
[0024] providing the above ligand;
[0025] Inorganic particles and a solvent are provided and mixed with the ligand to obtain a composite material.
[0026] Optionally, in some embodiments of the present application, the mass ratio of the inorganic particles to the ligand is (3-18):4; and / or
[0027] The temperature at which the inorganic particles, the ligand and the solvent are mixed is 100° C. to 160° C.; and / or
[0028] The inorganic particles, the ligand and the solvent are mixed for 4 hours to 10 hours; and / or
[0029] The solvent includes one or more of dimethylformamide, dimethylacetamide, and γ-butyrolactone; and / or
[0030] After the inorganic particles, the ligands and the solvent are mixed, a precipitant is added to precipitate the composite material. The precipitant includes one or more of acetone, methanol, ethanol, isopropanol and n-propanol.
[0031] Correspondingly, an embodiment of the present application further provides a light-emitting device, comprising a stacked anode, a light-emitting layer and a cathode, wherein the material of the light-emitting layer comprises the above-mentioned composite material, or comprises the composite material prepared by the above-mentioned preparation method.
[0032] Optionally, in some embodiments of the present application, the thickness of the light-emitting layer is 3nm to 40nm; and / or
[0033] The preparation method of the light-emitting layer comprises: mixing the composite material with a second solvent to obtain a light-emitting material dispersion, and placing the light-emitting material dispersion on the anode to obtain a light-emitting layer; the second solvent comprises one or more of toluene, o-xylene, m-xylene, p-xylene, mesitylene, dichloromethane, chloroform, chlorobenzene, p-dichlorobenzene, and tetrachloroethylene; in the light-emitting material dispersion, the mass concentration of the composite material is 5 mg / mL to 100 mg / mL; and / or
[0034] The materials of the anode and the cathode include one or more of metal, carbon material and metal oxide respectively; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a metal oxide electrode or a composite electrode with a metal sandwiched between doped or undoped transparent metal oxides, the material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or
[0035] The light-emitting device further comprises a hole functional layer, which is arranged between the anode and the light-emitting layer. The hole functional layer comprises one or more of a hole injection layer and a hole transport layer. The materials of the hole injection layer and the hole transport layer respectively comprise 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N, N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazolyl-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylenevinylene) , poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N '-Di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, transition metal oxides, transition metal sulfides, transition metal tin compounds, doped or undoped zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, barium titanate, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, hydroxyquinoline compounds or one or more thereof; and / or
[0036] The light-emitting device also includes an electronic functional layer, which is arranged between the light-emitting layer and the cathode. The electronic functional layer includes one or more of an electron injection layer and an electron transport layer. The materials of the electron injection layer and the electron transport layer respectively include one or more of doped or undoped semiconductor particles, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds. The semiconductor particles include one or more of zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, and barium titanate. The doped elements include one or more of indium, gallium, aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium.
[0037] Correspondingly, the present application also provides a display device, which includes the above-mentioned light-emitting device.
[0038] The composite material provided by the present application includes inorganic particles and ligands connected to the inorganic particles, wherein the ligands have a cyclic conjugated structure and a functional group, and the functional group can achieve coordination connection with the inorganic particles; compared with ligands with similar cyclic non-conjugated structures, the ligands with cyclic conjugated structures have lower energy due to charge delocalization caused by resonance and hybridization, making the composite material less susceptible to oxidation, and the ligands in an excited state can interact with the energy levels of the inorganic particles to promote the luminescence of the light-emitting device, thereby improving the luminescence efficiency of the light-emitting device and extending the service life of the light-emitting device. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0040] Figure 1 is a flow chart of a method for preparing a composite material provided in an embodiment of the present application;
[0041] Figure 2 is a schematic structural diagram of a light-emitting device provided in an embodiment of the present application;
[0042] Reference numerals:
[0043] Anode 10; light emitting layer 20; cathode 30; hole functional layer 40; electron functional layer 50. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0045] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.
[0046] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0047] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0048] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0049] The technical solution of this application is as follows:
[0050] In a first aspect, an embodiment of the present application provides a composite material, comprising inorganic particles and a ligand connected to the inorganic particles, wherein the ligand has a structural formula as shown in formula (I):
[0051]
[0052] Wherein, Ar includes substituted or unsubstituted C10-C24 fused ring aromatic groups, substituted or unsubstituted C5-C24 fused ring heteroaromatic groups; the heteroatoms in the fused ring heteroaromatic groups include one or more of oxygen atoms, nitrogen atoms or sulfur atoms; the substituted substituents are selected from one or more of C1-C10 alkyl groups, C1-C10 alkenyl groups, C1-C10 alkynyl groups, C1-C10 alkoxy groups, halogen atoms, D, -CN, -NO2;
[0053] X is selected from one or more of an amino group, a carboxyl group, a thiol group or a phosphate group.
[0054] It should be noted that the fused aryl group and the fused heteroaryl group have a conjugated planar ring system, and Ar has a conjugated structure. In other words, all atoms of the fused aryl group and the fused heteroaryl group are on the same plane. Further, all atoms in Ar are on the same plane.
[0055] The composite material described in the present application includes inorganic particles and ligands connected to the inorganic particles, wherein the ligands have a cyclic conjugated structure and a functional group, and the functional group can achieve coordination connection with the inorganic particles; compared with ligands with similar cyclic non-conjugated structures, the ligands with cyclic conjugated structures have lower energy due to charge delocalization caused by resonance and hybridization, making the composite material less susceptible to oxidation, and the ligands in an excited state can interact with the energy levels of the inorganic particles to promote the luminescence of the light-emitting device, thereby improving the luminescence efficiency of the light-emitting device and extending the service life of the light-emitting device.
[0056] In some embodiments, the ligand is attached to the inorganic particle by a coordinate covalent bond.
[0057] In some embodiments, in the composite material, the mass ratio of the inorganic particles to the ligand is (5-15):1, for example, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, etc. Within the mass ratio range, the composite material has good solubility and high luminous efficiency.
[0058] Furthermore, in the composite material, the mass ratio of the inorganic particles to the ligand is (8-9):1, for example, 8.1:1, 8.2:1, 8.3:1, 8.4:1, 8.5:1, 8.6:1, 8.7:1, 8.8:1, or 8.9:1.
[0059] In some embodiments, the fused ring aromatic group is composed of a cyclic group, wherein the cyclic group includes a benzene ring and One or more of .
[0060] In some embodiments, the aromatic ring in the fused-ring heteroaryl group includes one or more of a benzene ring, a furan ring, a pyran ring, a thiophene ring, a pyridine ring, and a pyrrole ring.
[0061] In some embodiments, the heteroatoms in the fused ring heteroaryl group include one or more of oxygen atoms, nitrogen atoms or sulfur atoms. It should be noted that the substituted carbon atoms in Ar are carbon atoms that are not shared by two or more cyclic structures and carbon atoms that are not connected to the X functional group.
[0062] In some embodiments, the substituted fused ring aromatic group or the substituent in the fused ring aromatic group is selected from one or more of C1-C10 alkyl, C1-C10 alkenyl, C1-C10 alkynyl, C1-C10 alkoxy, halogen atom, D, -CN, -NO2. For example, the alkyl group includes methyl, ethyl, propyl, butyl, isopropyl, etc., the alkenyl group includes vinyl, propenyl, etc., the alkoxy group includes methoxy, ethoxy, etc., and the halogen atom includes fluorine atom, chlorine atom, bromine atom, etc.
[0063] Further, the substituted substituent is selected from one or more of C1-C6 alkyl, C1-C6 alkenyl, C1-C6 alkynyl, C1-C6 alkoxy, halogen atom, D, -CN, -NO2. Exemplarily, the alkyl includes methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, pentyl or hexyl, etc., the alkenyl includes vinyl, allyl, butenyl, etc., the alkoxy includes methoxy, ethoxy, n-propoxy, iso-propoxy, n-butoxy, n-pentoxy and n-hexoxy, etc., and the halogen atom includes fluorine atom, chlorine atom, bromine atom, etc.
[0064] In some embodiments, X is one of an amino group, a carboxyl group, a thiol group, or a phosphate group.
[0065] In some embodiments, the fused ring aromatic group or fused ring heteroaromatic group in Ar includes 2-4 substituted or unsubstituted aromatic rings or heteroaromatic rings, for example, 3. Within the range of the number, the ligand is easily soluble and the luminescence efficiency of the composite material can be improved.
[0066] Furthermore, when Ar includes two substituted or unsubstituted aromatic rings or heteroaromatic rings, Ar includes naphthyl and a double-fused five-membered ring group.
[0067] In some embodiments, when Ar includes three substituted or unsubstituted aromatic or heteroaromatic rings, Ar includes anthracenyl, fluorenyl, phenanthrenyl, indolyl, quinolyl, benzofuranyl, or benzothiophenyl.
[0068] In some embodiments, when Ar includes 4 substituted or unsubstituted aromatic or heteroaromatic rings, Ar includes pyrenyl and naphthacene.
[0069] In some embodiments, when Ar includes two substituted or unsubstituted aromatic rings or heteroaromatic rings, the ligand has one of the following structural formulas:
[0070]
[0071] In some embodiments, when Ar includes 3 substituted or unsubstituted aromatic rings or heteroaromatic rings, the ligand has one of the following structural formulas:
[0072]
[0073] In some embodiments, when Ar includes 4 substituted or unsubstituted aromatic rings or heteroaromatic rings, the ligand has one of the following structural formulas:
[0074]
[0075] In some embodiments, the ligand is one or more of 1-aminofluorene, 1-carboxylfluorene, 1-mercaptofluorene, and 1-phosphofluorene.
[0076] In some embodiments, the average particle size of the inorganic particles is 3 nm to 20 nm, for example, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, etc. Within the average particle size range, the inorganic particles have good luminescent properties and are easy to disperse.
[0077] In some embodiments, the inorganic particles do not contain lead, cadmium, or mercury. It is understood that lead, cadmium, and mercury can damage the environment and impair the function of human organs. The composite material does not contain lead, cadmium, or mercury, which can improve the safety of the composite material and the light-emitting device.
[0078] In some embodiments, the material of the inorganic particles includes a quantum dot luminescent material, and the quantum dot luminescent material includes one or more of a single structure quantum dot, a core-shell structure quantum dot and a perovskite semiconductor material. The material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot are independently selected from one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds. The II-VI group compounds include one or more of ZnO, ZnS, ZnSe, ZnTe, ZnSeS, ZnSeTe, and ZnSTe. The IV-VI group compounds include one or more of SnS, SnSe, SnTe, SnSeS, SnSeTe, and SnSTe. The III-V group compounds include GaN, GaP, GaAs, GaSb, AlP, AlAs, AlSb, InN, InP, InAs, One or more of InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound comprises one or more of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material comprises a doped or undoped inorganic perovskite semiconductor or an organic-inorganic hybrid perovskite semiconductor, the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ions, M is a divalent metal cation, including Sn 2+ , Cu 2+ 、Ni 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMY3, wherein B is an organic amine cation, including CH3(CH2) n- 2NH3+ or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation, including Sn 2+ , Cu 2+ 、Ni 2+ Cr 2+ , Mn 2+ 、Co 2 + , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, Y is a halogen anion, including Cl - Br - ,I - One or more of .
[0079] Second, see Figure 1 The present application also provides a method for preparing a composite material, comprising:
[0080] S11. Provide a ligand having a structural formula as shown in formula (I):
[0081]
[0082] Wherein, Ar includes substituted or unsubstituted C10-C24 fused ring aromatic group, substituted or unsubstituted C5-C24 fused ring heteroaromatic group; the heteroatom in the fused ring heteroaromatic group includes one or more of oxygen atom, nitrogen atom or sulfur atom; the substituted substituent is selected from one or more of C1-C10 alkyl, C1-C10 alkenyl, C1-C10 alkynyl, C1-C10 alkoxy, halogen atom, D, -CN, -NO2; X is selected from one or more of amino, carboxyl, thiol or phosphate;
[0083] S12, providing inorganic particles and a solvent, and mixing them with the ligand to obtain a composite material.
[0084] The preparation method of the composite material provided in the present application has a simple preparation process; and by adding a ligand having a cyclic conjugated structure and a functional group to modify the inorganic particles, the functional group can achieve a coordination connection with the inorganic particles; compared with similar cyclic non-conjugated structures, the cyclic conjugated structure has lower energy due to charge delocalization due to resonance and hybridization, making the composite material less susceptible to oxidation, and the ligand in an excited state can interact with the energy level of the inorganic particles to promote the luminescence of the light-emitting device.
[0085] In the S11:
[0086] The ligands are as described above and will not be described in detail here.
[0087] In S12:
[0088] In some embodiments, the mass ratio of the inorganic particles to the ligand is (3-18):4, for example, 5:4, 6:4, 7:4, 8:4, 9:4, 10:4, 11:4, 12:4, 13:4, 14:4, 15:4, 16:4, 17:4, etc. Within the molar ratio range, the inorganic particles and the ligand have good dispersibility in the solvent.
[0089] It should be noted that, in some embodiments, the inorganic particles can be first mixed with the first solvent and then the ligand can be added to mix; in other embodiments, the ligand can be first mixed with the solvent and then the inorganic particles can be added to mix; in still other embodiments, the inorganic particles can be mixed with the solvent and the ligand at the same time; in other embodiments, the inorganic particles and the ligand can be first mixed with the solvent separately to obtain an inorganic particle solution and a ligand solution, and then the inorganic particle solution and the ligand solution are mixed.
[0090] In some embodiments, in the inorganic particle solution, the mass concentration of the inorganic particles is 1 mg / mL to 6 mg / mL, for example, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3 mg / mL, 3.5 mg / mL, 4 mg / mL, 4.5 mg / mL, 5 mg / mL, 5.5 mg / mL, etc. Within the mass concentration range, the dissolution of the inorganic particles is facilitated.
[0091] In some embodiments, in the ligand solution, the mass concentration of the ligand is 5 mg / mL to 50 mg / mL, for example, 10 mg / mL, 15 mg / mL, 20 mg / mL, 25 mg / mL, 30 mg / mL, 35 mg / mL, 40 mg / mL, 45 mg / mL, etc. Within the mass concentration range, the binding rate and binding yield of the ligand to the inorganic particles can be increased.
[0092] In some embodiments, the solvent includes one or more of dimethylformamide, dimethylacetamide, and γ-butyrolactone.
[0093] In some embodiments, the temperature for mixing the inorganic particles, the ligand and the solvent is 100°C to 160°C, for example, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, etc. The mixing time is 4h to 10h, for example, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, etc. In this way, under the mixing conditions, the combination of the inorganic particles and the ligand can be promoted to improve the reaction efficiency.
[0094] In some embodiments, after the mixing, a precipitant is added to precipitate the composite material.
[0095] In some embodiments, the precipitating agent comprises one or more of acetone, methanol, ethanol, isopropanol, and n-propanol.
[0096] It can be understood that the preparation method of the inorganic particles is a prior art method in the art, for example, a chemical solution growth method, a sol-gel method, an epitaxial growth method, and an electric field confinement method.
[0097] In at least one embodiment, when the inorganic particles are ZnO, the method for preparing ZnO includes: providing a zinc salt solution and an alkaline solution, mixing and reacting them to obtain ZnO.
[0098] In some embodiments, the zinc salt includes but is not limited to one or more of zinc acetate, dimethyl zinc, diethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, zinc oleate, zinc stearate, zinc undecylenate, zinc hydroxide, and zinc peroxide.
[0099] In some embodiments, the solvent in the zinc salt solution includes one or more of dimethyl sulfoxide (DMSO), acetone, acetophenone, tetrahydrofuran (THF), N,N-dimethylformamide (DMF), ethyl acetate, pyrrole, ethanol, butyric acid, and cresol.
[0100] In some embodiments, in the zinc salt solution, the concentration of the zinc salt is 0.5 mmol / L to 10 mmol / L, for example, 1 mmol / L, 2 mmol / L, 3 mmol / L, 4 mmol / L, 5 mmol / L, 6 mmol / L, 7 mmol / L, 8 mmol / L, 9 mmol / L, etc. Within the concentration range, the zinc salt has good dispersibility, short reaction time, and the size of the obtained ZnO nanoparticles is uniform.
[0101] In some embodiments, the alkali in the alkali solution includes one or more of tetramethylammonium hydroxide, potassium hydroxide, lithium hydroxide, sodium hydroxide, ammonium hydroxide, ethylenediamine, ethanolamine, diethanolamine, triethanolamine, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, and tetrabutylammonium hydroxide.
[0102] In some embodiments, the solvent in the alkali solution includes one or more of ethanol, methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, and glycerol.
[0103] In some embodiments, in the alkali solution, the concentration of the alkali is 0.1 mmol / L to 8 mmol / L, for example, 1 mmol / L, 2 mmol / L, 3 mmol / L, 4 mmol / L, 5 mmol / L, 6 mmol / L, 7 mmol / L, etc. Within the concentration range, the alkali has good dispersibility in the solvent, the reaction time is short, and the size of the obtained ZnO nanoparticles is uniform.
[0104] In some embodiments, the volume ratio of the zinc salt solution to the alkali solution is 2:(1-4), for example, 2:2, 2:3, etc. Within the volume ratio range, the reaction between the zinc salt and the alkali can be promoted.
[0105] In some embodiments, the method of mixing the zinc salt solution and the alkali solution comprises: dropping the zinc salt solution into the alkali solution.
[0106] In some embodiments, the dripping rate is 10 mL / h to 100 mL / h, for example, 15 mL / h, 20 mL / h, 25 mL / h, 30 mL / h, 35 mL / h, 40 mL / h, 45 mL / h, 50 mL / h, 60 mL / h, 70 mL / h, etc. Within the dripping rate range, the zinc salt solution and the alkali solution are facilitated to fully mix and react.
[0107] In some embodiments, the temperature of the mixed reaction of the zinc salt solution and the alkali solution is 50°C to 80°C, for example, 52°C, 55°C, 58°C, 60°C, 62°C, 65°C, 68°C, 70°C, 72°C, 75°C, 78°C, etc. The time of the mixed reaction of the zinc salt solution and the alkali solution is 0.5h to 10h, for example, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, etc. In this way, under the conditions of the mixed reaction, the zinc salt and the alkali can fully react. Inorganic particles with uniform particle size are prepared.
[0108] In some embodiments, after the zinc salt solution and the alkali solution are mixed and reacted, a precipitant is added to precipitate the ZnO.
[0109] In some embodiments, the precipitant comprises one or more of acetone, n-hexane, toluene, n-heptane, tetrahydrofuran, benzene, and dichloromethane.
[0110] Third, see Figure 2 The embodiment of the present application further provides a light-emitting device, comprising a stacked anode 10, a light-emitting layer 20 and a cathode 30, wherein the material of the light-emitting layer 20 comprises the above-mentioned composite material.
[0111] The light-emitting device provided in the present application, the composite material used in the light-emitting layer 20 includes inorganic particles and ligands connected to the inorganic particles, the ligands have a cyclic conjugated structure and a functional group, and the functional group can achieve coordination connection with the inorganic particles; compared with similar cyclic non-conjugated structures, the cyclic conjugated structure has lower energy due to charge delocalization due to resonance and hybridization, making the composite material less prone to oxidation, and the ligands in an excited state can interact with the energy levels of the inorganic particles to promote the luminescence of the light-emitting device.
[0112] In some embodiments, the light emitting device is a blue light emitting device.
[0113] In some embodiments, the materials of the anode 10 and the cathode 30 include one or more of metal, carbon material and metal oxide respectively; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a metal oxide electrode or a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, and the material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2. Here, “ / ” represents a stacked structure. For example, AZO / Ag / AZO represents a composite electrode including an AZO layer, an Ag layer and an AZO layer stacked in sequence.
[0114] In some embodiments, the light emitting device further includes a hole functional layer 40, and the hole functional layer is disposed between the anode 10 and the light emitting layer 20. The hole functional layer 40 includes one or more of a hole injection layer and a hole transport layer.
[0115] In some embodiments, the materials of the hole injection layer and the hole transport layer are respectively but not limited to 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, (Carbazole-9-yl) triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino) triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl) diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylene vinylene), poly(phenylene vinylene), poly[2-methoxy-5-(2-ethyl [(2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N ,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, transition metal oxides, transition metal sulfides, transition metal tin compounds, doped or undoped zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, barium titanate, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, hydroxyquinoline compounds or one or more thereof.
[0116] In some embodiments, the light emitting device further comprises an electronic functional layer 50. The electronic functional layer 50 is disposed between the light emitting layer 20 and the cathode 30. The electronic functional layer 50 comprises one or more of an electron injection layer and an electron transport layer.
[0117] In some embodiments, the materials of the electron injection layer and the electron transport layer include one or more of doped or undoped semiconductor particles, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds. The semiconductor particles include one or more of zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, and barium titanate, and the doped elements include one or more of indium, gallium, aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium.
[0118] In some embodiments, the thickness of the light emitting layer 20 is 3 nm to 40 nm, for example, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 36 nm, 37 nm, 38 nm, etc.
[0119] In some embodiments, the preparation method of the light-emitting layer 20 can adopt conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction, anodization, electrolytic deposition, and coprecipitation. The physical method includes physical coating and solution method, among which the physical coating method includes: thermal evaporation coating, electron beam evaporation coating, magnetron sputtering, multi-arc ion coating, physical vapor deposition, atomic layer deposition, pulsed laser deposition, etc.; the solution method can be spin coating, printing, inkjet printing, doctor blade coating, printing, dip-coating, immersion, spraying, roller coating, casting, slit coating, strip coating, etc.
[0120] In at least one embodiment, the light-emitting layer 20 is prepared by a solution method. Specifically, the composite material is mixed with a solvent to obtain a light-emitting material dispersion, and the light-emitting material dispersion is disposed on the anode 10 to obtain the light-emitting layer 20 .
[0121] In some embodiments, the solvent includes one or more of toluene, o-xylene, m-xylene, p-xylene, mesitylene, dichloromethane, chloroform, chlorobenzene, p-dichlorobenzene, and tetrachloroethylene.
[0122] In some embodiments, in the luminescent material dispersion, the mass concentration of the composite material is 5 mg / mL to 100 mg / mL, for example, 10 mg / mL, 20 mg / mL, 30 mg / mL, 40 mg / mL, 50 mg / mL, 60 mg / mL, 70 mg / mL, 80 mg / mL, 90 mg / mL, etc. Within the mass concentration range of the composite material, it is beneficial for the composite material to be uniformly dispersed in the solvent, and it is beneficial for the luminescent material dispersion to prepare a thin film and form a luminescent layer.
[0123] In a fourth aspect, the present application also relates to a display device, which includes the light-emitting device.
[0124] The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptops, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, among which smart wearable devices can be, for example, smart bracelets, smart watches, virtual reality (VR) helmets, etc.
[0125] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.
[0126] Example 1
[0127] This embodiment provides a composite material, including ZnO nanoparticles and 1-aminofluorene connected to the ZnO nanoparticles, wherein the mass ratio of the ZnO nanoparticles to the 1-aminofluorene is 8.5:1. The preparation method of the composite material is as follows:
[0128] 30 mL of 3 mmol / L anhydrous zinc acetate solution was added dropwise to 20 mL of 4 mmol / L tetramethylammonium hydroxide solution at a rate of 40 mL / h, wherein the solvent of the anhydrous zinc acetate was dimethyl sulfoxide and the solvent of the tetramethylammonium hydroxide solution was ethanol, and the reaction was carried out at 70°C for 2 h to obtain ZnO nanoparticles with a particle size of 10 nm, which were precipitated by acetone and dispersed in ethanol, and purified three times in a cycle; 1200 mg of ZnO nanoparticles were dissolved in 300 mL of dimethylformamide to obtain an inorganic particle dispersion with a mass concentration of 4 mg / mL;
[0129] 400 mg of 1-aminofluorene was dissolved in 40 mL of dimethylformamide to obtain a ligand dispersion with a mass fraction of 10 mg / mL. The ligand dispersion was added to the inorganic particle dispersion, and the temperature was raised to 130° C. to react for 5 hours. Then, acetone was added thereto to precipitate the composite material to obtain a composite material.
[0130] Embodiment 2-7
[0131] The present Example 2-7 is substantially the same as Example 1, with the only difference being that in Example 2-7, 1-aminofluorene is replaced by 1-carboxyfluorene, 1-mercaptofluorene, 1-phosphofluorene, 1-aminonaphthalene, 1-aminophenanthrene, and 1-aminopyrene, respectively.
[0132] Wherein, the preparation method of 1-aminophenanthrene comprises:
[0133] 10mmol of phenanthrene and 10mmol of liquid bromine were heated to reflux in 10mL of carbon tetrachloride for 6h, and 1-bromophenanthrene was separated by chromatographic column after cooling. 11mL of 1mol / L sodium azide in tetrahydrofuran solution was added dropwise to 10mL of 1mol / L 1-bromophenanthrene in tetrahydrofuran solution at -70°C, and 11mL of 1mol / L lithium aluminum hydride in tetrahydrofuran solution was added after reaction for 30min, and the mixture was returned to room temperature after reaction for 30min, and 1mL of water was added, and 1-aminophenanthrene was purified by chromatographic column.
[0134] The preparation method of 1-carboxyfluorene comprises:
[0135] 10mmol of fluorene and 10mmol of liquid bromine were heated to reflux in 10mL of carbon tetrachloride for 6h, and 1-bromofluorene was separated by chromatographic column after cooling. 10mL of 1mol / L 1-bromofluorene in tetrahydrofuran was cooled to -70°C, and 10mL of 1mmol of commercial Grignard reagent was added dropwise thereto. After reacting for 20min, excess dry ice and 0.1mL of water were added thereto respectively, and 1-carboxyfluorene was obtained after heating to room temperature and purification was performed by chromatographic column.
[0136] The preparation method of 1-mercaptofluorene comprises:
[0137] 10mmol of fluorene and 10mmol of liquid bromine were heated to reflux in 10mL of carbon tetrachloride for 6h, and 1-bromofluorene was separated by chromatographic column after cooling. 5mL of 2mol / L thiourea / dimethylformamide solution was added to 10mL of 1mol / L 1-bromofluorene dimethylformamide solution at room temperature, and 5mL of 2mol / L sodium hydroxide aqueous solution was added after heating to 50℃. After the reaction, 1-mercaptofluorene was purified by chromatographic column.
[0138] The preparation method of 1-phosphofluorene comprises:
[0139] 10 mmol of fluorene and 10 mmol of liquid bromine were heated to reflux in 10 mL of carbon tetrachloride for 6 h, and 1-bromofluorene was separated by chromatographic column after cooling. 10 mL of 1 mol / L 1-bromofluorene / dimethylformamide solution was mixed with 1.1 mmol of red phosphorus, heated to 150 ° C for 6 h, cooled, filtered, and the solution was purified by chromatographic column to obtain 1-phosphofluorene.
[0140] Examples 8-10
[0141] The present embodiments 8-10 are substantially the same as embodiment 1, with the only difference being that in embodiments 8-10, the ZnO nanoparticles are replaced by ZnSe nanoparticles, ZnS nanoparticles, and ZnSeS nanoparticles, respectively.
[0142] Embodiment 11
[0143] This embodiment is substantially the same as Embodiment 1, except that the particle size of the ZnO nanoparticles in this embodiment is 3 nm.
[0144] Example 12
[0145] This embodiment is substantially the same as Embodiment 1, except that the particle size of the ZnO nanoparticles in this embodiment is 20 nm.
[0146] Example 13
[0147] This example is basically the same as Example 1, except that, in this example, 300 mg of ZnO nanoparticles are dissolved in 300 mL of dimethylformamide to obtain an inorganic particle dispersion with a mass concentration of 1 mg / mL; and 400 mg of 1-aminofluorene is dissolved in 40 mL of dimethylformamide to obtain a ligand dispersion with a mass concentration of 10 mg / mL.
[0148] Embodiment 14
[0149] This example is basically the same as Example 1, except that, in this example, 1800 mg of ZnO nanoparticles are dissolved in 300 mL of dimethylformamide to obtain an inorganic particle dispersion with a mass concentration of 6 mg / mL; and 400 mg of 1-aminofluorene is dissolved in 40 mL of dimethylformamide to obtain a ligand dispersion with a mass concentration of 10 mg / mL.
[0150] Embodiment 15
[0151] This embodiment is substantially the same as Embodiment 1, except that the reaction temperature of the ligand dispersion and the inorganic particle dispersion in this embodiment is 100°C.
[0152] Example 16
[0153] This embodiment is substantially the same as Embodiment 1, except that the reaction temperature of the ligand dispersion and the inorganic particle dispersion in this embodiment is 160°C.
[0154] Embodiment 17
[0155] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the reaction time of the ligand dispersion and the inorganic particle dispersion is 4 hours.
[0156] Embodiment 18
[0157] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the reaction time of the ligand dispersion and the inorganic particle dispersion is 10 h.
[0158] Comparative Example 1
[0159] This comparative example is substantially the same as Example 1, except that the material of this comparative example is original ZnO nanoparticles, that is, not compounded with 1-aminofluorene.
[0160] Comparative Example 2
[0161] This comparative example is substantially the same as Example 1, except that the particle size of the ZnO nanoparticles in this comparative example is 2 nm.
[0162] Comparative Example 3
[0163] This comparative example is substantially the same as Example 1, except that the particle size of the ZnO nanoparticles in this comparative example is 25 nm.
[0164] Comparative Example 4
[0165] This comparative example is substantially the same as Example 1, except that the ligand of the ZnO nanoparticles in this comparative example is aniline.
[0166] Device Example 1
[0167] This device embodiment provides a quantum dot light emitting diode, and the preparation method is as follows:
[0168] Providing an ITO glass, cleaning the ITO glass with a cleaning agent to remove stains on the surface, then ultrasonically cleaning the ITO glass with deionized water, isopropyl acetone, acetone and deionized water for 20 minutes respectively, and then drying with nitrogen to obtain an ITO anode with a thickness of 110 nm;
[0169] Providing a PEDOT:PSS solution, spin coating at a rotation speed of 4000 rpm, heating on a heating table at 100°C for 30 min, to prepare a 100 nm hole injection layer;
[0170] 40 μL of TFB solution was taken with a pipette and slowly dripped on the hole injection layer for spin coating at a speed of 4000 rpm for 30 seconds, followed by annealing at a temperature of 140°C for 15 minutes to obtain a 70 nm hole transport layer;
[0171] The composite material of Example 1 was dissolved in toluene to obtain a luminescent material dispersion with a mass concentration of 40 mg / mL, and spin-coated at a speed of 3500 rpm for 45 seconds, followed by annealing at a temperature of 120° C. for 12 minutes to obtain a 20 nm quantum dot luminescent layer;
[0172] A 30 mg / mL 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline dispersion was placed on the quantum dot light-emitting layer and spin-coated at a speed of 5000 rpm for 30 seconds, followed by annealing at a temperature of 120° C. for 10 minutes to obtain a 40 nm electron transport layer.
[0173] The device was placed in a vapor deposition chamber and a layer of metallic silver was thermally evaporated through a mask plate to obtain a 60nm cathode;
[0174] The device was heat treated at 120° C. for 15 min and packaged to obtain a quantum dot light emitting diode.
[0175] Device Examples 2 to 18
[0176] Device Examples 2 to 18 are substantially the same as Device Example 1, except that the composite materials of Examples 2 to 18 are respectively used to prepare the quantum dot light-emitting layers.
[0177] Device Comparison Examples 1 to 4
[0178] Device Comparative Examples 1 to 4 are substantially the same as Device Example 1, except that the composite materials of Comparative Examples 1 to 4 are respectively used to prepare quantum dot light-emitting layers.
[0179] The quantum dot light emitting diodes in device embodiments 1 to 18 and device comparative examples 1 to 4 were tested for emission wavelength, half-peak width, maximum external quantum efficiency, and lifespan T50@100nit, and the test results are shown in Table 1. It should be noted that the half-peak width can reflect the luminescence purity of the quantum dot light emitting diode. The lower the half-peak width, the purer the luminescence purity, and the higher the half-peak width, the lower the luminescence purity, which will cause the color of the quantum dot light emitting diode to change and distort.
[0180] Among them, the emission wavelength and half-peak width refer to the standard: SJ 2658.12-1986-Test method for semiconductor infrared light-emitting diodes: peak emission wavelength and spectrum half-width are tested;
[0181] The maximum external quantum efficiency was measured by controlling the efficiency test system built by QE PRO spectrometer, Keithley 2400, and Keithley 6485 through LabView, with a driving current of 2 mA.
[0182] The test method for life span T50@100nit is: using a 128-channel life span test system customized by Guangzhou New Vision Company. The system architecture is a constant voltage and constant current source to drive QLED, test the change in voltage or current, and the photodiode detector and test system test the brightness (photocurrent) change of QLED. The brightness meter test calibrates the brightness (photocurrent) of QLED to obtain the time it takes for the initial brightness of the light-emitting diode to decay to 50%, and the driving current is 2mA; T50@100nit refers to the time it takes for the initial brightness of the device to decay to 50%, and it is converted to the aging time at 100nit.
[0183] Table 1
[0184]
[0185]
[0186] From Table 1, we can see that:
[0187] It can be seen from device embodiments 1 to 7 and device comparative examples 1 and 4 that the composite material containing the ligand provided by the present solution is used as the luminescent material, so that the quantum dot light-emitting diode can emit blue light with higher purity, the maximum external quantum efficiency is greater than 1.5%, and T50@100nit is greater than 12000. The use of different ligands has little effect on the performance of the quantum dot light-emitting diode. However, the quantum dot light-emitting diode of device comparative example 1 does not undergo ligand exchange, emits green light, has a large half-peak width, low luminescence purity, color distortion, and the maximum external quantum efficiency and T50@100nit are also much lower than those of the quantum dot light-emitting diodes of device embodiments 1 to 7. Device comparative example 4 uses aniline as a ligand of ZnO, and the number of rings is only 1. Its luminescence purity, maximum external quantum efficiency and T50@100nit are better than those of device comparative example 1, but the effect is still far behind that of device embodiments 1 to 7, indicating that the ligand provided by the present solution can effectively improve the performance of ZnO, thereby improving the luminescence purity and luminescence efficiency of the quantum dot light-emitting diode, and extending the service life.
[0188] It can be seen from device example 1, device examples 8 to 10 and device comparative example 1 that replacing the inorganic ZnO particles with inorganic ZnSe, ZnS or ZnSeS particles respectively has no significant effect on the performance of the quantum dot light-emitting diodes, and the performance of the quantum dot light-emitting diodes of device example 1 and device examples 8 to 10 is greater than that of the quantum dot light-emitting diode of device comparative example 1;
[0189] It can be seen from device example 1, device examples 11-12 and device comparative examples 2-3 that when the average particle size of the inorganic particles is 3nm-20nm, the maximum external quantum efficiency and T50@100nit of the quantum dot light-emitting diode far exceed the quantum dot light-emitting diodes with inorganic particles of 2nm and 25nm, and the luminescence purity of the inorganic particles with a particle size of 25nm is not significantly different from that of the quantum dot light-emitting diodes of device example 1 and device examples 11-12, and the inorganic particles with a particle size of 2nm do not emit light. This is because the agglomeration problem of inorganic particle nanoparticles with a particle size of less than 3nm is very serious, resulting in the quantum dot light-emitting diode not emitting light, and the preparation process of inorganic particle nanoparticles with a particle size greater than 20nm is difficult, and the luminescence performance is poor;
[0190] It can be seen from device example 1, device examples 13 to 14 and device comparative example 1 that changing the ratio of inorganic particles to ligands, while still maintaining it within an appropriate range, has no significant effect on the luminescence purity and maximum external quantum efficiency of the quantum dot light-emitting diode, but the T50@100nit of device example 1 with a moderate ratio is significantly higher than that of the quantum dot light-emitting diodes of device examples 13 to 14; in general, the performance of the quantum dot light-emitting diodes using the ligands provided by this solution is greater than that of the quantum dot light-emitting diodes of device comparative example 1;
[0191] It can be seen from device example 1, device examples 15 to 18 and device comparison example 1 that changing the reaction conditions of the inorganic particles and the ligands, while still maintaining them within an appropriate range, has no significant effect on the performance of the quantum dot light-emitting diodes; and the luminescence purity, maximum external quantum efficiency and service life of the quantum dot light-emitting diodes of device example 1 and device examples 15 to 18 are all better than those of the quantum dot light-emitting diodes of device comparison example 1.
[0192] The composite materials and preparation methods thereof, light-emitting devices, and display devices provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the methods and core ideas of the present application. At the same time, for technical personnel in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A composite material, characterized in that: It includes inorganic particles and ligands connected to the inorganic particles, wherein the ligand has a structural formula as shown in formula (I): Wherein, Ar includes substituted or unsubstituted C10-C24 fused ring aromatic groups, substituted or unsubstituted C5-C24 fused ring heteroaromatic groups; the heteroatoms in the fused ring heteroaromatic groups include one or more of oxygen atoms, nitrogen atoms or sulfur atoms; the substituted substituents are selected from one or more of C1-C10 alkyl groups, C1-C10 alkenyl groups, C1-C10 alkynyl groups, C1-C10 alkoxy groups, halogen atoms, D, -CN, -NO2; X is selected from one or more of an amino group, a carboxyl group, a thiol group or a phosphate group.
2. The composite material according to claim 1, characterized in that The condensed ring aromatic group is composed of a cyclic group, and the cyclic group includes a benzene ring, One or more of; and / or The aromatic ring in the fused-ring heteroaryl group includes one or more of a benzene ring, a furan ring, a pyran ring, a thiophene ring, a pyridine ring, and a pyrrole ring; and / or X is selected from one of an amino group, a carboxyl group, a thiol group or a phosphate group; and / or The substituted substituent is selected from one or more of C1-C6 alkyl, C1-C6 alkenyl, C1-C6 alkynyl, C1-C6 alkoxy, halogen atom, D, -CN, -NO2.
3. The composite material according to claim 2, characterized in that Ar has one of the following structural formulas:
4. The composite material according to any one of claims 1 to 3, characterized in that: The ligand has one of the following structural formulas:
5. The composite material according to claim 1, characterized in that In the composite material, the mass ratio of the inorganic particles to the ligand is (5-15):1; and / or The average particle size of the inorganic particles is 3nm to 20nm; and / or The material of the inorganic particles includes quantum dot luminescent materials, and the quantum dot luminescent materials include one or more of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials. The material of the single structure quantum dots, the core material of the core-shell structure quantum dots and the shell material of the core-shell structure quantum dots are independently selected from one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds. The II-VI group compounds include one or more of ZnO, ZnS, ZnSe, ZnTe, ZnSeS, ZnSeTe and ZnSTe. The IV-VI group compounds include one or more of SnS, SnSe, SnTe, SnSeS, SnSeTe and SnSTe. The III-V group compounds include GaN, GaP, GaAs, GaSb, AlP, AlAs, AlSb, InN, InP, InAs, InSb , GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound includes one or more of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material includes a doped or undoped inorganic perovskite semiconductor or an organic-inorganic hybrid perovskite semiconductor, the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ions, M is a divalent metal cation, including Sn 2+ , Cu 2+ 、Ni 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMY3, wherein B is an organic amine cation, including CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation, including Sn 2+ , Cu 2+ 、Ni 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, Y is a halogen anion, including Cl - Br - ,I - One or more of .
6. The composite material according to claim 5, characterized in that In the composite material, the mass ratio of the inorganic particles to the ligand is (8-9):1; and / or The average particle size of the inorganic particles is 8nm to 15nm.
7. A method for preparing a composite material, characterized in that: include: Providing a ligand for the composite material according to any one of claims 1 to 6; Inorganic particles and a solvent are provided and mixed with the ligand to obtain a composite material.
8. The preparation method according to claim 7, characterized in that: The mass ratio of the inorganic particles to the ligand is (3-18):4; and / or The temperature at which the inorganic particles, the ligand and the solvent are mixed is 100° C. to 160° C.; and / or The inorganic particles, the ligand and the solvent are mixed for 4 hours to 10 hours; and / or The solvent includes one or more of dimethylformamide, dimethylacetamide, and γ-butyrolactone; and / or After the inorganic particles, the ligands and the solvent are mixed, a precipitant is added to precipitate the composite material, and the precipitant includes one or more of acetone, methanol, ethanol, isopropanol and n-propanol.
9. A light emitting device, characterized in that: The invention comprises a stacked anode, a light-emitting layer and a cathode, wherein the material of the light-emitting layer comprises the composite material according to any one of claims 1 to 6, or comprises the composite material prepared by the preparation method according to any one of claims 7 to 8.
10. The light emitting device according to claim 9, characterized in that: The thickness of the light-emitting layer is 3nm to 40nm; and / or The preparation method of the light-emitting layer comprises: mixing the composite material with a second solvent to obtain a light-emitting material dispersion, and placing the light-emitting material dispersion on the anode to obtain a light-emitting layer; the second solvent comprises one or more of toluene, o-xylene, m-xylene, p-xylene, mesitylene, dichloromethane, chloroform, chlorobenzene, p-dichlorobenzene, and tetrachloroethylene; in the light-emitting material dispersion, the mass concentration of the composite material is 5 mg / mL to 100 mg / mL; and / or The materials of the anode and the cathode include one or more of metal, carbon material and metal oxide respectively; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a metal oxide electrode or a composite electrode with a metal sandwiched between doped or undoped transparent metal oxides, the material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or The light-emitting device further comprises a hole functional layer, which is arranged between the anode and the light-emitting layer. The hole functional layer comprises one or more of a hole injection layer and a hole transport layer. The materials of the hole injection layer and the hole transport layer respectively comprise 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N, N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazolyl-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylenevinylene) , poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N '-Di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, transition metal oxides, transition metal sulfides, transition metal tin compounds, doped or undoped zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, barium titanate, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, hydroxyquinoline compounds or one or more thereof; and / or The light-emitting device also includes an electronic functional layer, which is arranged between the light-emitting layer and the cathode. The electronic functional layer includes one or more of an electron injection layer and an electron transport layer. The materials of the electron injection layer and the electron transport layer respectively include one or more of doped or undoped semiconductor particles, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds. The semiconductor particles include one or more of zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, and barium titanate. The doped elements include one or more of indium, gallium, aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium.
11. A display device, characterized in that: The light emitting device comprises the light emitting device according to any one of claims 9 to 10.
Citation Information
Cited By
Composite electrode material, preparation method and application in transparent supercapacitor
CN120878470A